Synthesis and characterization of dirhodium(II) formamidinyl complexes: preliminary studies as catalyst precursors for the allylic oxidation of cyclohexene - Casimiro, Anna (Department of Chemistry, 2019)
A series of symmetrical substituted formamidine-type ligands, (L1, L2 and L3) were synthesized via a solvent-free reaction, in which ethanol is produced as by-product. The ligands were characterized as to their spectroscopic and solid-state properties via FT-IR, UV-Vis and NMR spectroscopies showing a prototropic tautomerism for L2 and L3. The acetate precursor complexes Rh2(O2CR)4 where R = CH3 (C1) or CF3 (C2) were synthetized and fully characterized. Reaction of C2 with an excess of formamidine ligand yields the complexes C3, C4, C5 and C6 via a solventless reaction. The 2-fluorophenyl complex, [Rh2(di-2F-pf)4] complex, C5 was structurally characterized by single crystal X-Ray crystallography revealing a paddle-wheel type complex. Allylic oxidation reactions using the binuclear Rh complexes showed that these are active for cyclohexene conversion giving a range of products. Solvent coordination could have an effect on the catalytic behaviour of the complexes, with acetonitrile being the best solvent probably due to the solubility properties of complexes. Under these conditions, the allylic oxidation of cyclohexene produced enone as major product. The best result in terms of selectivity were obtained with C1, C4, C5 and C6 which yielded only 2-cyclohexene-1-one.